The Lac au Renard Tephra Cluster: a record of Lochkovian (Lower Devonian) volcanism in the Indian Point Formation, Gaspe Peninsula, Quebec, Canada - Ebert, James R.; Matteson, Damon K. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2019)
Approximately twenty tephra beds, comprising the Lac au Renard Tephra Cluster (new), occur in the Rosebush Cove and Petit Portage members of the Indian Point Formation (Chaleurs Group) on the Gaspe Peninsula of Quebec, Canada. The tephra beds range in thickness from <1.0 cm to 82 cm and occur in a mudrock-dominated sequence with coarser tempestite interbeds. Mineralogically and texturally graded accumulations of phenocrysts mark the bases of the thickest tephra beds. Early diagenetic concretions in one composite tephra preserve pre-compaction fabrics and original hypocrystalline textures with microphenocrysts and devitrified glass shards. The presence of plagioclase, quartz, K-feldspar, biotite, apatite, and zircon suggest a rhyolitic source. The coarseness of the microphenocrysts in the basal accumulations, along with the abundance and thickness of the tephras, suggest that deposition in the Gaspe area was in a proximal position relative to the volcanic source. The zonal graptolites Monograptus praehercynicus and Monograptus aequabilis ssp. from the Petit Portage Member indicate a middle Lochkovian age for the Lac au Renard Tephra Cluster of the Indian Point Formation. Correlation with the tephra cluster that includes the Judds Falls Bentonite in the New Scotland Formation and other possible tephras in the Kalkberg Formation (Helderberg Group) of New York and the Corriganville and Mandata formations of Pennsylvania is likely. The graptolite fauna of the Indian Point and probable correlations to New York may provide additional biostratigraphic constraints on a U–Pb zircon radiometric age determination of 417.6 Ma from New York that has been used to estimate the age of the Silurian–Devonian boundary.